2018
DOI: 10.1016/j.newast.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Wolf–Rayet stars, black holes and the first detected gravitational wave source

Abstract: The recently discovered burst of gravitational waves GW150914 provides a good new chance to verify the current view on the evolution of close binary stars. Modern population synthesis codes help to study this evolution from two main sequence stars up to the formation of two final remnant degenerate dwarfs, neutron stars or black holes (Masevich & Tutukov, 1988). To study the evolution of the GW150914 predecessor we use the "Scenario Machine" code presented by Lipunov, Postnov & Prokhorov (1996). The scenario m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 113 publications
0
13
0
Order By: Relevance
“…One of them is the stronger stellar winds of massive stars lead to a rapid and substantial increase of the orbital separation, so these stars cannot fill their Roche lobes. There exist several observational facts that argue against scenarios with strong stellar winds (they can be found in Bogomazov et al, 2018), but we make calculations also for scenarios B and C to show that in a wide range of evolutionary parameters the isolated binary evolution can describe all detected gravitational wave bursts. 3 See also (Pavlovskii et al, 2017).…”
Section: The Scenario Machinementioning
confidence: 90%
See 2 more Smart Citations
“…One of them is the stronger stellar winds of massive stars lead to a rapid and substantial increase of the orbital separation, so these stars cannot fill their Roche lobes. There exist several observational facts that argue against scenarios with strong stellar winds (they can be found in Bogomazov et al, 2018), but we make calculations also for scenarios B and C to show that in a wide range of evolutionary parameters the isolated binary evolution can describe all detected gravitational wave bursts. 3 See also (Pavlovskii et al, 2017).…”
Section: The Scenario Machinementioning
confidence: 90%
“…Antonini et al (2016). Nevertheless, Bogomazov et al (2018) showed that it is possible to produce a massive binary BH (that can merge within an appropriate interval of time) with or without the common envelope phase as the result of the isolated binary evolution.…”
Section: Necessity Of a Common Envelope To Get A Compact Pre-supernov...mentioning
confidence: 99%
See 1 more Smart Citation
“…We consider here a 130 M star finishing its hydrogen burning evolution in a close binary with a black hole of ∼ 60 M with an initial orbital separation of 300 R , or about 2 × 10 13 cm. Such a configuration is reasonable for the progenitors of LIGO sources (Bogomazov et al 2018). The initial black hole mass is reasonable for the range of reaction rates and rotation rates considered in this paper.…”
Section: Super-eddington Accretionmentioning
confidence: 65%
“…At the center of the candidate hypernova remnant there is an X-ray source-IC10 X-1-a binary consisting of a WR star and a massive (23-24 M ) black hole. In recent years, interest in such objects has increased due to the detection of gravitational waves from merging black holes (see discussion in Bogomazov et al, 2018).…”
Section: Emission-line Stars and Unique Objectsmentioning
confidence: 99%